2014
DOI: 10.1002/ddr.21234
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of American Ginseng Against Premature Ovarian Failure in a Rat Model

Abstract: Preclinical Research Premature ovarian failure (POF) is defined by the WHO as the loss of physiological ovarian function before the age of 40. The effect of American ginseng and its underlying mechanisms in preventing and treating premature ovarian failure (POF) was studied in female Sprague-Dawley rats where POF was induced by ip administration of 4-vinylcyclohexene diepoxide (VCD). Rat behavior, serum hormone levels, ovarian and uterine size, pathological features, and ovarian tissue expression of genes asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…Both studies have demonstrated a decrease in circulating 17b-estradiol and an increase in follicle-stimulating hormone (FSH) 30 days after 4-VCD treatment. The dose of 4-VCD administration and the time post-treatment evaluated in these studies were quite different from ours [37,38], which could explain the different results. The study conducted by Reis et al [15] considered the periestropause period (analogous to perimenopause in women) around to 80 days after the beginning of 4-VCD treatment.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Both studies have demonstrated a decrease in circulating 17b-estradiol and an increase in follicle-stimulating hormone (FSH) 30 days after 4-VCD treatment. The dose of 4-VCD administration and the time post-treatment evaluated in these studies were quite different from ours [37,38], which could explain the different results. The study conducted by Reis et al [15] considered the periestropause period (analogous to perimenopause in women) around to 80 days after the beginning of 4-VCD treatment.…”
Section: Discussioncontrasting
confidence: 60%
“…The effectiveness of 4-VCD administration in the VCD and VCD + DEX groups was consistent with previous studies demonstrating a reduction in the ovary weight 30 days after the completion of 4-VCD administration in adult rats (80 mg/kg, b. w., i.p.) [37,38]. Both studies have demonstrated a decrease in circulating 17b-estradiol and an increase in follicle-stimulating hormone (FSH) 30 days after 4-VCD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…8C). While these three types of biochemical measurements were combined, PCA and heatmap results (Figs 7D and 8D) showed that the model group was separated from both the control and AG-administrated irradiated groups, indicating that American ginseng had the radioprotection effects due to its antioxidant and immunomodulatory properties and the modulation of hypothalamic–pituitary–gonadal (HPG) system 56,57 . However, the radioprotection effects varied among different cultivation regions of AGs.…”
Section: Resultsmentioning
confidence: 99%
“…VCD specifically causes gradual apoptotic cell death of primordial and primary follicles resulting in induced ovarian failure without evidence of systemic toxicity, resulting in an endocrine state that closely mimics the natural modeling the transition to menopause in women. 9…”
Section: Chemical Induction Of Ovarian Failurementioning
confidence: 99%
“…The rats are considered acyclic with persistent diestrus phase, which is dominated by leukocytes, while control animals showed regular estrous cycles. 9…”
Section: Vaginal Smearmentioning
confidence: 99%